Eco-Hermeneutics and Scriptural Interpretation: Reimagining Sacred Texts for an Environmental Theology of Care - Mangihut Siregar; Ahmad Sufaidi; Arditya Prayogi; Ali Banaeian Esfahani (Green Philosophy: International Journal of Religious Education and Philosophy, 2025)
This study explores the application of eco-hermeneutics, an interdisciplinary approach combining ecological thought and scriptural interpretation, to sacred texts such as the Bible, Quran, and Vedas. Eco-hermeneutics seeks to reinterpret traditional religious teachings to emphasize ecological responsibility, interconnectedness, and the moral obligation of humans to protect the environment. The analysis identifies key ecological themes within sacred scriptures, including creation care, stewardship, and the intrinsic value of nature. Interviews with theologians and environmental ethicists provide practical insights into how eco-hermeneutical interpretations can be applied in contemporary religious contexts, offering a fresh perspective on environmental ethics rooted in religious teachings. This approach challenges anthropocentric views, which have historically positioned humans as dominators of nature, and instead advocates for an ecocentric understanding of the environment. The findings highlight the potential of eco-hermeneutics to inspire faith-based responses to the ecological crises, urging religious communities to adopt these interpretations to foster environmental stewardship. However, challenges and resistance from traditional religious communities are identified, particularly concerning entrenched views on human supremacy over nature. The study also explores the implications of eco-hermeneutics for religious education, suggesting that its integration into religious curricula could promote a theology of care and responsibility toward the environment. The paper concludes by calling for further research on the practical applications of eco-hermeneutics, particularly in how these teachings can be incorporated into religious practices and community actions, contributing to global sustainability efforts.